Franz Kline : the artist's materials - Rogge, Corina E. (Artist's materials., 2022)
"The first comprehensive study of Franz Kline's methods and techniques and the eighth book in the Artist's Materials series, which explores the unique and unconventional materials used by contemporary artists and the challenges encountered by professionals tasked with conserving their works"--